2022
DOI: 10.1016/j.ultsonch.2021.105899
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the microjet velocity and cavitation erosion on a copper plate produced by a spherical cavity focused transducer at the high hydrostatic pressure

Abstract: Highlights The Proposed multi-microjet impact model suitable for high hydrostatic pressures. Cavitation erosion experiments can be conducted in an ultrasonic cavitation system composed of a spherical cavity focused transducer with high acoustic energy in a sub-wavelength focal region. Quantitative analysis of cavitation pit morphology can be achieved through the proposed microjet impact model. A microjet velocity inversion model was prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…4 and Fig. 6 ), as observed in our study, is speculated to be induced by smaller-sized and faster cavitation microjets pinning on the Cu plate generated under higher , in line with the theoretical result of our previous work [13] . The microstructure of cavitation erosion on the Cu plate can give us some important information, such as the velocity, the radii of cavitation microjets, and the spatial distribution of cavitation bubbles inside the bubble cloud, which can hardly be directly observed via optical means due to their microscopic and ultra-fast nature.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…4 and Fig. 6 ), as observed in our study, is speculated to be induced by smaller-sized and faster cavitation microjets pinning on the Cu plate generated under higher , in line with the theoretical result of our previous work [13] . The microstructure of cavitation erosion on the Cu plate can give us some important information, such as the velocity, the radii of cavitation microjets, and the spatial distribution of cavitation bubbles inside the bubble cloud, which can hardly be directly observed via optical means due to their microscopic and ultra-fast nature.…”
Section: Resultssupporting
confidence: 93%
“…Later, researchers demonstrated that cavitation erosion is a general phenomenon in the fields of aviation, navigation, hydraulic machinery, and so on, which is the primary mechanism responsible for the damage of fluid machinery, such as the hydraulic turbine of the hydropower station, the rudder blade or arm of the high-speed vessel, and the afterburner fuel pump of the aero-engine [9] , [10] , [11] , [12] . Severe damage to these fluid machinery results in very high costs for repair [13] . Therefore, the issue of cavitation erosion attracts extensive attention both in academic research and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as a punch-less forming technology, a work-piece only can be formed by laser-induced cavitation within the need for optics devices, which brings some issues of cost and accuracy. 13 In addition, Xiong et al 14 established a micro-jet impact model and a micro-jet velocity inversion model to quantitatively characterize the cavitation erosion process and cavitation degree, respectively, to specify the water jet cavitation forming technology. However, their proposed models are only reliable when the cavitation pit diameter-to-depth ratio is approximate to 1 which cannot adapt to various situations.…”
Section: Introductionmentioning
confidence: 99%